The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.7205/milmed.169.9.681
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of a Ruptured Ectopic Pregnancy in a Combat Support Hospital during Operation Iraqi Freedom: Case Report and Critique of a Field-Ready Sonographic Device

Abstract: This case report describes a novel diagnostic approach for ectopic pregnancy in a combat environment. We diagnosed a ruptured ectopic pregnancy at our combat support hospital by using the SonoSite 180 Plus ultrasound device (SonoSite, Bothell, WA). The live ectopic pregnancy was immediately identified and the entire pelvic anatomy was easily assessed within 5 minutes. The SonoSite ultrasound device proved to be easy to use, durable, and reliable. It produced high-quality images in a variety of applications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When used in a field hospital in Iraq, a portable ultrasound device was used in conditions of limited space, high ambient temperature and light, and often under battery power [13]. Other authors in a similar military environment found portable ultrasound to have “great utility in the field or during patient transport” [14]. …”
Section: Introductionmentioning
confidence: 99%
“…When used in a field hospital in Iraq, a portable ultrasound device was used in conditions of limited space, high ambient temperature and light, and often under battery power [13]. Other authors in a similar military environment found portable ultrasound to have “great utility in the field or during patient transport” [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The authors noted that the scans improved their diagnostic capacity and helped prevent unnecessary evacuation to higher-level facilities out of theater solely for radiologic imaging. In a recent case report of a ruptured ectopic pregnancy diagnosed in a field hospital setting with portable ultrasound, the authors subjectively described good image quality and durability throughout the deployment of the device (28). The device in this study was exposed to heat, wind, and sand, and the authors report that it was well suited to use in a field hospital or during transport.…”
Section: Feasibility Of Field Deploymentmentioning
confidence: 85%
“…Despite the controversy in objectively defining the image quality [30], [31], there is no doubt that differential diagnosis was confirmed when a more advanced clinical ultrasound unit was used, which inevitably produced higher quality ultrasound images for clinical diagnosis. Studies have suggested that PUS provides a significant benefit that can drastically alter the disposition and treatment in patients at Accident and Emergency Departments, Intensive Care Units, small-scale hospitals and remote location settings [30], [32][34]. In view of the concerns raised from zoological and aquarium settings, a PUS could play an adequate role in improving a variety of veterinary procedures by providing a real-time, non-invasive clinical tool.…”
Section: Discussionmentioning
confidence: 99%